2013
DOI: 10.1021/jp3105858
|View full text |Cite
|
Sign up to set email alerts
|

Y(III) Interactions with Guanine Oligonucleotides Covalently Attached to Aqueous/Solid Interfaces

Abstract: The binding of Y(III) ions to surface-immobilized single-stranded 20-mers of guanine was studied using the Eisenthal χ((3)) technique and AFM. The free energy of binding for Y(III) to the G(20) sequence was found to be -39.5(8) kJ/mol. Furthermore, yttrium binds much more strongly to surface-immobilized oligonucleotides than the divalent metals previously reported. At maximum surface coverage, Y(III) ion densities range between one to three ions bound per strand. Comparatively, Mg(II) binds to the G(20)-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…This process, known as electric field induced second harmonic (EFISH) generation, has been demonstrated to be well suited to the determination of p K a values of protonation sites at oxide–water interfaces, the measurement of the isoelectric point, , and, as shown later in this review, the measurement of cation–DNA binding energies. All of these studies rely on measurment of increased signal that occurs with charge buildup at the interface.…”
Section: Overview Of Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…This process, known as electric field induced second harmonic (EFISH) generation, has been demonstrated to be well suited to the determination of p K a values of protonation sites at oxide–water interfaces, the measurement of the isoelectric point, , and, as shown later in this review, the measurement of cation–DNA binding energies. All of these studies rely on measurment of increased signal that occurs with charge buildup at the interface.…”
Section: Overview Of Techniquesmentioning
confidence: 99%
“…Most research on the interaction of ions with DNA at interfaces has been done by the SHG χ (3) method since its signal is related to the charge of the interface. In 2011 the Geiger group demonstrated that the Eisenthal method was well-suited to study metal ion interaction with ssDNA at the silica–water interface .…”
Section: Biomolecular Structure At Solid–liquid Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tracking the change of I SHG with increasing electrolyte concentration can produce valuable interface specific parameters, such as surface charge density, interfacial potential, and subsequently thermodynamic binding parameters. By applying an appropriate surface complexation model, the χ (3) method has been successfully utilized to determine these important interface specific parameters for a variety of systems including oxides, ,,, DNA, and lipid bilayers …”
Section: Introductionmentioning
confidence: 99%